Complete mitochondrial genome organization of Schizothorax richardsonii (Gray, 1832). (June 2014) - Goel, Chirag; Sati, Jyoti; Barat, Ashoktaru; Patiyal, R. S.; Ali, S.; Sahoo, Prabhati Kumari
Abstract The complete mitochondrial genome of Schizothorax richardsonii, an endemic coldwater fish of Himalayas, was determined for the first time. The genome is 16, 592 bp in length and consists of 13 protein coding genes, 22 tRNAs, 2 rRNA genes and one putative control region. The gene organization and its order were similar to other vertebrates. The overall base composition was as follows: A: 29.9%, G: 17.7%, C: 26.9%, T: 25.5%, A + T content 55.4% and the G + C content 44.6%. The control region contains a microsatellite; (TA)13 exists between 16, 469 and 16, 494 bp. This study will provide the rationale for the management and conservation of the snow trout.